Comparative study and performance evaluation of steel moment resisting frames design with: Force-based design and performance-based plastic design. (September 2022) - Biradar, Bapugouda B.; Shirkol, A I; Bush, Rc
Abstract: Incremental Dynamic Analysis (IDA), Nonlinear Response History Analysis (NLRHA) and Nonlinear Static Pushover Analysis (NSPA) has been carried out to evaluate seismic performance of Steel Moment Resisting Frames (SMRF). SMRF's are used as the lateral resisting systems which consist of columns and beams joined by welding or using high strength bolts or combination of both. The resistance offered to the lateral forces is due to rigid frame action which develops bending moment and shear force in the frame members and joints. The 9-storey SMRF is been evaluated for two frames designed by Force Based Design (FBD) method and Performance Based Plastic Design (PBPD) method. The FBD frame is designed by using codal provision of ASCE 7 (American Based Seismic Code) and AISC (American Institute of Steel Construction) whereas PBPD frame is designed as per proposed work of Lee and Goel (2001) in which energy balance equation and pre-selected yield mechanism is considered. The evaluation study showed that the PBPD method for steel moment resisting frame is significantly more efficient in achieving a certain inelastic displacement/ductility for given seismic hazards compared to the existing design standards/specification for this system. By Nonlinear Static Pushover Analysis (NSPA) the PBPD method has achieved the target yield drift of 1.11% and FBD method has achieved 1.22% where the assumed yield drift was 1%. From NLRHA the percentage difference in achieved ductility factor for frame design by FBD method is 46.28% whereas for PBPD method it is 16.81%. From IDA inter storey drift is observed maximum in AISC design frame compared to PBPD design frame. Therefore, PBPD method frames responded as intended in design with much improved performances over those of the corresponding FBD method.